Sustainability of the Sawah Surjan Agricultural Systems in Depok Village, Panjatan Subdistrict, Kulonprogo Regency, Yogyakarta Special Province - R Rijanta (Forum Geografi, 2018)
The south coastal region of Yogyakarta Province (YSP) in Indonesia has inherited a unique farming system called sawah surjan, which is considered as a cultural heritage that demonstrates a form of local wisdom in managing land resources with poor drainage. The local residents have succeeded in realizing their desire of making the farming system ecologically stable and capable of providing a decent living. As a cultural heritage, however, sawah surjan has been under an increasing threat of conversion resulting from the infrastructure development and spreading of urban developments. This study assessed the prospect of sawah surjan in the rural household economy and its sustainability within the context of changing wider environment. To do so, a household survey was conducted covering 41 farmer households in Depok Village, Panjatan Sub-district, Kulonprogo Regency, Yogyakarta Special Province where the existence of sawah surjan is threatened by the large-scale investments. The research show that sawah surjan contributes to employment generation, diverse sources of income, food security, and income redistribution. It is generally sustainable but the excessive use of pesticides and chemical fertilizers will have adverse effects on its sustainability. The research confirms that the most significant threat is the infrastructural development, especially the prospective construction of a new international airport as increased land prices may lead to uncontrolled conversion of sawah surjan into non-agricultural uses. This is also in coincidence with the stagnant regeneration of farmers in the area that lead to a bleak future of the system.